Apoptosis induction by Pleurotus sajor-caju (Fr.) Singer extracts on colorectal cancer cell lines - Finimundy, Tiane C. (2018)
Pleurotus sajor-caju (PSC) is an edible mushroom used in food supplements, presenting antitumor properties through induction of cell death pathways. The PSC potential against colorectal cancer was analyzed by exposing HCT116wt cells to different PSC extracts. The PSC n-hexane extract (PSC-hex) showed the highest cytotoxicity effect (IC50 value 0.05 mg/mL). The observed cytotoxicity was then associated to apoptosis-promoting and cell cycle-arrest pathways. PSC-hex was able to induce apoptosis related to breakdown of mitochondrial membrane potential and ROS generation. The absence of cytotoxicity in HTC116-p53 and HTC116-Bax cells, alongside with an increase in p53, Bax and Caspase-3 expression, and decrease in Bcl-2 expression, supports that the proapoptotic effect is probably induced through a p53 associated pathway. PSC-hex induced cell cycle arrest at G2/ M in HCT116wt without cytotoxicity in HTC116-p21 cells. These findings suggest that a p21/p53 cell cycle regulation pathway is probably disrupted by compounds present on PSC-hex. Identification of the major components was then performed with ergosta-5,7,22-trien-3β-ol representing 30.6% of total weight. In silico docking studies of ergosta-5,7,22-trien-3β against Bcl-2 were performed and results show a credible interaction with the Bcl-2 hydrophobic cleft. The results show that PSC-hex can be used as supplementary food for adjuvant therapy in colorectal carcinoma.